Thiadiazolo‐Azaacenes. Issue 24 (26th March 2019) - Müller, Matthias; Koser, Silke; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: This work reports the synthesis and characterization of bis‐ and tetrakis(thiadiazolo)‐appended di‐ and tetraazaacenes, displaying up to seven catenated benzene/pyrazine rings. The targets are obtained by condensation of benzo‐bis(thiadiazole)‐4, 5‐dione with aromatic di‐ and tetraamines. The condensation products—up to a heptacene‐like species—are stable but can be insoluble. Soluble derivatives are readily processible, but do not show enhanced electron affinities, as the two or four attached benzothiadiazole units are effectively resonance‐separated from the acene body, maximizing the number of Clar‐sextets. Abstract : Stabilizing wings : A tetraazaheptacene stabilized by four thiadiazolo‐"aprons".